(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article discusses the management of innovative processes at an enterprise, methods for assessing the innovative activity of an industrial enterprise, as well as a methodology for assessing the effectiveness of innovative processes.